Relationship between Facet Joint Tropism with Lumbar Disc Herniation at A Particular Motion Segment - Shrestha, Sandesh; Lakhey, Rajesh Bahadur; Paudel, Sharma; Paudel, Sushil (Journal of Nepal Health Research Council, 2023)
Background: Lumbar disc herniation is one of the important and common causes of low back pain. There are various modifiable and non-modifiable risk factors for the development of lumbar disc herniation. Any change in the orientation or asymmetry of the facet joint i.e. facet tropism may lead to abnormal shearing stress on the intervertebral disc and may lead to development of disc herniation. Methods: This is a cross-sectional observational study of 46 patients aged 18-40 years with clinical features of Prolapsed Intervertebral Disc and Magnetic Resonance Imaging evidence of single level prolapsed disc who presented to Tribhuvan University Teaching Hospital from December 2019 to June 2021. MRI measurement of facet tropism of normal level (L4-L5 or L5-S1) adjacent to herniated level was used for comparison. The p - value ? 0.05 was considered statistically significant. Overall association of tropism with lumbar disc herniation in affected and normal level combined and at each individual level was studied using McNemar Test. Results: We found a highly significant association of facet tropism with lumbar disc herniation (p-value <0.001). Considering the individual levels, at L4-L5 level, the association between facet tropism and lumbar disc herniation was highly significant (p-value <0.001). However, at L5-S1 level the association was not significant (p-value <0.388). Conclusions: The results of our study show strong association between FT and lumbar disc herniation at a particular motion segment. Keywords: Facet tropism; inter-vertebral disc prolapse; lumbar disc herniation; magnetic resonance imaging